A new effective stress intensity factor approach to determine thickness-independent fatigue crack growth rate curves. (October 2022) - Calvín, Giovanna; Escalero, Mikel; Zabala, Haritz; Muñiz-Calvente, Miguel
Abstract: In this paper, it is experimentally demonstrated that the use of standardised methods to characterise the crack growth rate curves of metallic materials conforms to thickness-dependent results. To correct that dependency, the contribution of the stress intensity factor and crack closure on the effective stress intensity factor range is assessed by comparing analytical and numerical alternatives of calculation, which consider crack shapes experimentally determined. The findings reveal that (i) the crack closure is a thickness-independent edge effect, which allow developing analytical equations to determine the crack closure distribution along the thickness, and that (ii) the distribution of the effective stress intensity factor range is more influenced by crack closure than the maximum stress intensity factor. With the aim of obtaining a superposition of fatigue crack growth curves from different specimen thicknesses, an approach to calculate thickness-independent effective stress intensity factor range ( Δ K eff, TI ) is proposed and demonstrated. Highlights: Standardised procedures to characterise the crack growth rate laws of metallic materials are thickness-dependent. New approach to calculate thickness-independent effective stress intensity factor range is proposed and demonstrated. The superposition of fatigue crack growth curves from different specimen thicknesses is achieved. It is numerically demonstrated that the plasticity induced crack closure is a thickness-independent edge effect.